Subtle Changes in Myocardial Work Indices Assessed by 2D-Speckle Tracking Echocardiography Are Linked with Pathological LV Remodeling and MACEs Following an Acute Myocardial Infarction Treated by Primary Percutaneous Coronary Intervention - Diana-Aurora Arnautu; Alexandru Gheorghiu; Sergiu-Florin Arnautu; Mirela-Cleopatra Tomescu; Claudiu-Daniel Malita; Christian Banciu; Cristina Vacarescu; Ioana Ionac; Silvia Luca; Dragos Cozma; Cristian Mornos; Dan Gaita; et al. (Diagnostics, 2023)
The goal of this study was to assess whether subtle changes in myocardial work indices may predict left ventricular (LV) remodeling and major cardiac events (MACEs) in patients with a first ST-elevation acute myocardial infarction (STEMI) and preserved LVEF after successful myocardial revascularization with PCI. Methods. Consecutive STEMI patients in sinus rhythm and with an LV ejection fraction ≥ 50% following a successful PCI were recruited. Conventional and two-dimensional speckle tracking echocardiography (2D-STE) was conducted within 36 h of the PCI and 3 months later. Patients having an increase of more than 20% in LV diastolic volume were included in the LV remodeling group. MACEs were noted throughout a four-year period of follow-up. Results: The study comprised 246 STEMI patients with a mean age of 66; 72% of whom were men. In 24% (58) of the patients, LV remodeling developed. These patients were older, more frequently hypertensive, and had a smoking history. They also exhibited significantly lower baseline and 3-month values for the myocardial global index (GWI), global constructive work (GCW), and global myocardial efficiency (GWE). The cut-off values of 1670 mmHg% for GWI and 83% for GWE were predictive of LV remodeling (p < 0.0001). During the four-year follow-up period, 19% of STEMI patients experienced a MACE, involving 15% from non-LV remodelers and 34% from LV remodelers (p = 0.01). The cut-off values for baseline GWI of 1680 mmHg% and baseline GWE of 84% had the best accuracy in predicting MACEs. In conclusion, non-invasive myocardial work indices offered a reproducible and accurate method to predict post-MI LV remodeling and MACEs.